STUDI TENTANG FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN STATUS KESEHATAN GIGI DAN MULUT SISWA SMK YAPENDA WIRADESA KABUPATEN PEKALONGAN - Imam Purnomo; Sri Lestari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Healthy is the result of 3 (three) condition they are, physique, mental and social that interact each other. Thus, status of dental health and mouth are also the result of interaction between physique,  mental  and  social.  Factors  that  affect  status  of  dental  health  and  mouth  are knowledge, kind  of consumed snacks, way to  brush teeth, way to  check teeth, and smoking habit. The purpose of the study is to find out factors related to dental health  students’ mouth of SMK Yapenda Wiradesa, Pekalongan regency. In conducting the research, the writer used survey  of  analytic  by  using  Cross  Sectional  approach.  The  populations  of  the  study  are  all students of SMK Yapenda Wiradesa. The sample are 208 populations that are taken by using simple  random  sampling.  The  instrument  in  this  study  is  questionnaire.  Data  analysis  was done univariately and bivariately using Chi Square test with α = 0,5. The result of the study shows that there is a relationship between knowledge (p = 0,032), kind of consumed snakcs (p = 0,000), way to brush teeth (p = 0,016) and status of dental and mouth heatlth students’ of SMK  Yapenda  Wiradesa,  Pekalongan  regency.  It  is  suggested  to  pay  attention  kind  of consumed snacks such as chocolate and candy reduced in amount, to brush teeth twice a day, to check to dentist, to visit school, and to hold counseling and checkup.Keywords : Knowledge,  kind  of  snacks,  way  to  brush  teeth,  Status  of  dental  health  and mouth.